7(c+3)=(8c-14)

Simple and best practice solution for 7(c+3)=(8c-14) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(c+3)=(8c-14) equation:


Simplifying
7(c + 3) = (8c + -14)

Reorder the terms:
7(3 + c) = (8c + -14)
(3 * 7 + c * 7) = (8c + -14)
(21 + 7c) = (8c + -14)

Reorder the terms:
21 + 7c = (-14 + 8c)

Remove parenthesis around (-14 + 8c)
21 + 7c = -14 + 8c

Solving
21 + 7c = -14 + 8c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-8c' to each side of the equation.
21 + 7c + -8c = -14 + 8c + -8c

Combine like terms: 7c + -8c = -1c
21 + -1c = -14 + 8c + -8c

Combine like terms: 8c + -8c = 0
21 + -1c = -14 + 0
21 + -1c = -14

Add '-21' to each side of the equation.
21 + -21 + -1c = -14 + -21

Combine like terms: 21 + -21 = 0
0 + -1c = -14 + -21
-1c = -14 + -21

Combine like terms: -14 + -21 = -35
-1c = -35

Divide each side by '-1'.
c = 35

Simplifying
c = 35

See similar equations:

| x^2+y^2+8x-6y+16=0 | | -3/4x-5/2=-5/8+2x | | (6x-7)(9x+4)=0 | | 1(15)=(6x)(4) | | 18m+8-16=118 | | 5x+3=3(2x+4) | | 19y=29/3 | | 0=-5x-2x | | 18m+8=118 | | 7x^2+8x-15=0 | | 7d+6b=27 | | .66x-.25=.6x+1 | | 1-4(7a-5)=-147 | | 8b-2b-y=4 | | -12t^2+12t+9=0 | | 12t^2-12t-9=0 | | +5=m/5-4 | | -3b+35+2b=95 | | 3/x-5 | | 6p+(2-2p)=6p | | 4(b-8)=7b+4 | | -8.4/2.4 | | 0.04x+0.07*(15000-x)=900 | | (6p+2)-2p=6p | | 84+17=5r+32 | | log(x)+log(x-10)=log(12x) | | 15d+20b=77.5 | | 3=3x-2x+5 | | 7(6+x)=6(2+x) | | 1/5+y=-7/10 | | 4.07-.61x=.82-5.16x | | -(8-5)-1= |

Equations solver categories